THE IMPACT OF A FLIPPED CLASSROOM ON STUDENTS SELF-REGULATION IN PRIMARY EDUCATION - Christiana Subagyo; J. Priyanto Widodo (Widya Mandala Surabaya Catholic University, 2024)
The research examines the impact of flipped classrooms students’ self-regulation of sixth- and fifth-grade students at SD Citra Berkat The Taman Dayu. The goal of the research is to determine how the flipped classroom approach affects students' ability to self-regulate by combining quantitative and qualitative analysis, identifying patterns, and making interpretations based on the findings. The research involves a survey of 52 elementary school students to evaluate self-regulation and perceptions of the flipped classroom. The findings are presented through interviews, observations, and surveys, indicating positive outcomes such as improved self-regulation, increased understanding of concepts, and enhanced student motivation to learn. The research's findings indicate that the implementation of the flipped classroom approach may enhance student self-regulation by providing opportunities for independent learning, time management, and task organization, ultimately enhancing academic achievement and understanding of concepts. The finding point to the flipped classroom approach's potential advantages for encouraging student involvement and self-regulation.